After imprisonment : special issue - Sarat, Austin (Bingley, U.K. : Emerald Publishing Limited, 2018)
Studies in Law, Politics, andSociety provides a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship. In this latest editionof this highly successful research series, chapters examine a diverse range oflegal issues and their impact on and intersections with society. This volume features a special section with papers dedicated to life after imprisonment. The chapters examine issues around offender rehabilitation, mass incarceration, and overcriminalization. Other papers included in this important volume address the shift in attitudes to solitary confinement (and the prospect of moving beyond solitary confinement measures) and private prison services. This volume brings together leading scholars and will be vital reading for all those researching in this subject area.
Prelims -- After solitary confinement: a new era of punishment? -- Planning for precarity? experiencing the carceral continuum of imprisonment and reentry -- Banking on rehab: private prison vendors and the reconfiguration of mass incarceration -- The collateral consequence conundrum: comparative genealogy, current trends, and future scenarios -- "$40 to Make sure": background check laws and the endogenous construction of criminal risk -- Churning through the system: how people engage with the criminal justice system when faced with short sentences -- Maximizing charges: overcriminalization and prosecutorial practices during the crime decline.
Print version record
Keywords: Ex-convicts -- Social conditions; Prisoners -- Deinstitutionalization; Imprisonment -- Social aspects; Law, Jurisprudence; Law & society